SCHOOL SELECTION CRITERIA FOR PARENTS- A SURVEY BASED APPROACH - Muhammad Hafeez (STKIP Rokania Pasir Pangaraian, 2021)
The quality of education is a significant element to develop a nation. A research based on survey method has been conducted to discover the causes of increasing admissions attitude of parents in private schools and to analyze the standards of private educational institutions. The research was designed on survey method by using comprehensive questionnaires for students, parents and teachers of private schools. Data was taken from the teachers, students and parents by questionnaires. Three private schools of district Dera Ghazi Khan were nominated for data collection. The questionnaires were containing 12 items for students, 19 items for parents and 9 items for teachers. The data was tabularized, interpreted and evaluated for results. The collected data was analyzed by percentage formula. The findings of research indicate that curriculum, facilities, teacher’s abilities, motivation to the students and examination systems of these private schools is adequate for most of the parents.